2017
DOI: 10.5539/ies.v10n5p13
|View full text |Cite
|
Sign up to set email alerts
|

The Characteristic of the Process of Students’ Metacognition in Solving Calculus Problems

Abstract: This article is the result of research aims to describe the patterns and characteristics of the process of metacognition student of mathematics in solving calculus problems. Description was done by looking at changes in awareness, evaluation, and regulation as components of metacognition. The changes in components of metacognition seen by the emergence of indicators for each indicator were described in descriptors. To see the changes, the researcher used the instrument consisting of calculus problems, metacogn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 1 publication
2
19
0
2
Order By: Relevance
“…The findings of this study also corroborate In'am (2016), Purnomo et al (2016) and Purnomo et al (2017) studies which suggest that students with high and medium capability have complete metacognition characteristics at each level. This means that elementary students in the informal deduction phase have metacognitive characteristics that are complete with medium or high math skills.…”
Section: Students' Metacognition Process In Checking Solutions Obtainedsupporting
confidence: 80%
See 1 more Smart Citation
“…The findings of this study also corroborate In'am (2016), Purnomo et al (2016) and Purnomo et al (2017) studies which suggest that students with high and medium capability have complete metacognition characteristics at each level. This means that elementary students in the informal deduction phase have metacognitive characteristics that are complete with medium or high math skills.…”
Section: Students' Metacognition Process In Checking Solutions Obtainedsupporting
confidence: 80%
“…It is related to the direct object of mathematics in building facts, concepts, operations, and principles. Gagne in Purnomo (2017) states that the direct object of mathematics is related to the ability of logical thinking, problem-solving, analytical thinking, positive-thinking to mathematics, dilligent, discipline will implicitly be obtained if someone learns mathematics. The statement means facts, concepts, operations, and principles as objects learned in mathematics can be done through learning.…”
Section: Introductionmentioning
confidence: 99%
“…The student will be aware of his thinking procedure and assess him or herself to the outcomes of his thought process so that it will reduce the mistake of a student to solve the problem. Purnomo and Nusantara (2017) have indicated that the concept of metacognition is an estimation of an individual's thinking, including metacognitive skills and metacognitive knowledge. In addition, Trisna et al.…”
Section: Theorymentioning
confidence: 99%
“…Several studies related to the student's metacognition process in mathematical problem solving have been done. Among them are Purnomo et al (2017) that high ability students are in complete and order of their characteristic of metacognition process, middle ability students are in complete and disorder of their characteristic of metacognition process, while low ability students are in incomplete of their characteristic of metacognition process. These studies are generally focused only on the process and characteristics of student's metacognition in solving mathematical problems.…”
Section: Introductionmentioning
confidence: 99%